Switching Condensates: The CTD Code Goes Liquid. Issue 1 (January 2020) - Portz, Bede; Shorter, James
Abstract : Condensates containing RNA polymerase II (Pol II) materialize at sites of active transcription. Young and coworkers now establish that C-terminal domain phosphorylation regulates Pol II partitioning into distinct condensates connected with transcription initiation or splicing. This advance hints that distinct condensates with specialized functional compositions might choreograph distinct stages of transcription.